2021
DOI: 10.18844/wjet.v13i4.6296
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of the digital skills of career education specialists during the provision of remote services

Abstract: The drastic and structural changes in the labour market and organisational environment is related not only to the COVID-19 pandemic and rapid technological development but also to general globalisation trends, demographic situations, deterioration, and dynamic changes at all levels of education, which emphasise the need for quality career education and guidance in secondary schools. This study aims to explore the digital self-assessment of career guidance professionals and also, to determine carrier guidance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Integrating career research modules into the curriculum has been shown to promote career exploration, understanding of the labour market, and the development of necessary skills for desired careers (Julien et al, 2023;Shen, 2021). Quality career education and guidance are crucial, especially in light of rapid technological advancements and globalization trends (Margevica-Grinberga & Smitiņa, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Integrating career research modules into the curriculum has been shown to promote career exploration, understanding of the labour market, and the development of necessary skills for desired careers (Julien et al, 2023;Shen, 2021). Quality career education and guidance are crucial, especially in light of rapid technological advancements and globalization trends (Margevica-Grinberga & Smitiņa, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Pese a que la razón principal de introducir las tecnologías es buscar la interactividad y el aumento de la motivación por parte del alumnado, se han encontrado escasas investigaciones que utilicen las tecnologías más innovadoras y participativas como los mundos virtuales y los juegos. Una de las principales implicaciones del estudio pone de manifiesto que es necesario invertir recursos humanos, materiales y económicos para la investigación y diseño de experiencias de aprendizaje virtual que apoyen la labor orientadora (Maree, 2021;Margevica-Grinberga y Smitiņa, 2021;Martínez-Clares, Casanova et al, 2020;Martínez-Clares, Martínez-Juárez y Pérez-Cusó, 2020;Supriyanto et al, 2019). Las tecnologías aportan un gran valor a los diferentes ámbitos de la orientación profesional, tanto para el autoconocimiento e intereses del sujeto, como en las habilidades sociales y para la carrera, el emprendimiento, la toma de decisiones, la búsqueda de información sobre salidas profesionales y orientación para el empleo, así como el conocimiento del entorno y mercado laboral.…”
Section: Conclusiones Y Discusiónunclassified
“…Usar activamente las tecnologías lleva asociado también una serie de desventajas como la accesibilidad al equipamiento y a la conexión para su uso y las competencias para hacer un uso correcto (Capano, 2020;Maree, 2021;Margevica-Grinberga y Smitiņa, 2021;Pantoja, 2004;Pantoja y Zwierewicz, 2008;Sobrado et al, 2012;Sobrado et al, 2013). Éstas se pueden contrarrestar, en gran medida, con una mayor dotación de recursos y formación para un empleo responsable de las mismas.…”
Section: Introductionunclassified
“…El desempeño y el esfuerzo de cada empleado ayuda al cumplimiento del logro de los resultados medibles. Margevica & Smitina (2021) argumentaron que el desempeño y el esfuerzo laboral varían de persona a persona, asegurando que afecta las habilidades, el trabajo en equipo, el liderazgo, la estimulación, el adiestramiento de los empleados y las actividades individuales.…”
Section: Lasunclassified